Weed research issues, challenges, and opportunities in India. (August 2020) - Rao, A.N.; Singh, Ravi Gopal; Mahajan, Gulshan; Wani, S.P.
Abstract: Agriculture is the major source of livelihood for nearly half of the Indian population. However, the productivity of crops is much lower than many countries and needs enhancement to produce ∼400 million tons of food grains for meeting food demands of a population of 1.7 billion by 2050. Diverse climatic conditions in India favor the most adopted weeds to prevail and cause severe crop yield losses. Weeds also degrade quality of the produce, raise cost of production; harbor and serve as alternate hosts to several insect pests and diseases. Parthenium hysterophorus L.; Phalaris minor Retz.; Leptochloa chinensis (L.) Nees.; Echinochloa spp.; weedy rice; Lantana camara L.; Chromolaena odorata (L.) R.M. King & H. Rob.; Mikania micrantha Kunth., are a few of many major weeds of concern currently in India. Weed management in India is critical to improve crops productivity by minimizing weeds caused crop yield losses and to alleviate other adverse effects of weeds in different ecosystems. In spite of the progress made in evolving weed management technologies for different crops and other ecosystems, weeds continue to be a concern in varying ecosystems. The real challenges of Indian weed research are: managing weeds in small farms; non availability of labor and mechanical tools; inadequate information on weed biology and shifts in weed flora; herbicide resistant weeds; lack of understanding on the impact of climate change on weeds and weed control; popularizing integrated weed management with herbicides use by ensuring safe use to avoid adverse effect on human health, environment and avoid weeds developing herbicide resistance and prevention of entry and management of alien invasive weeds. The greatest opportunity of Indian weed science is the potentiality of appropriate weed management technologies to substantially improve the crops productivity. Thus, weed scientists have a greater role to play in the development, popularization and adoption of location specific effective, economical and eco-friendly weed management technologies for different ecosystems of India. Highlights: Weeds continue to be major problem in different ecosystems of India. Major weed research issues are: weed biology, weed flora shifts and impact of climate change on weeds and weed management. Major challenge is popularizing integrated weed management with safe herbicides use and avoiding weeds herbicide resistance. The greatest opportunity is the potentiality of appropriate weed management technologies to improve crops productivity.